دور النفوذ الليبي في تشكيل العلاقات السياسية والاقتصادية بين مصر والمدن الفينيقية خلال حكم الأسرة الثانية والعشرين (945-730 ق.م) (Journal of Academic Research, 2024)
This study discusses the reign of the 22nd Dynasty in ancient Egypt (945-730 BCE), with a focus on the political and economic relations between Egypt and the Phoenician cities during the rule of Shoshenq I (954-924 BCE) and his successors. Through an analysis of the policies of Shoshenq I and his successors, the study reveals the role of these relations in enhancing Egypt's political and economic stability and their ongoing impact on the course of Egyptian history. The study also examines the challenges faced by the dynasty, including competition with the Kingdom of Israel led by the Prophet Solomon (963-923 BCE) and the Kingdom of Assyria, and how these challenges affected the dynasty's stability. Finally, the study highlights Shoshenq I's success in expanding Egypt's influence through his military campaigns, leading to significant political and economic stability and ensuring the loyalty of various parties.